The Pharmacology of Pain Associated With the Monoiodoacetate Model of Osteoarthritis - de Sousa Valente, João (Frontiers in Pharmacology, 2019)
The high incidence of osteoarthritis (OA) in an increasingly elderly population anticipates a dramatic rise in the number of people suffering from this disease in the near future. Because pain is the main reason patients seek medical help, effective pain management—which is currently lacking—is paramount to improve the quality of life that OA sufferers desperately seek. Good animal models are, in this day and age, fundamental tools for basic research of new therapeutic pathways. Several animal models of OA have been characterized, but none of them reproduces entirely all symptoms of the disease. Choosing between different animal models depends largely on which aspect of OA one aims to study. Here, we review the current understanding of the monoiodoacetate (MIA) model of OA. MIA injection in the knee joint leads to the progressive disruption of cartilage, which, in turn, is associated with the development of pain-like behavior. There are several reasons why the MIA model of OA seems to be the most adequate to study the pharmacological effect of new drugs in pain associated with OA. First, the pathological changes induced by MIA share many common traits with those observed in human OA (Van Der Kraan et al., 1989; Guingamp et al., 1997; Guzman et al., 2003), including loss of cartilage and alterations in the subchondral bone. The model has been extensively utilized in basic research, which means that the time course of pain-related behaviors and histopathological changes, as well as pharmacological profile, namely of commonly used pain-reducing drugs, is now moderately understood. Also, the severity of the progression of pathological changes can be controlled by grading the concentration of MIA administered. Further, in contrast with other OA models, MIA offers a rapid induction of pain-related phenotypes, with the cost-saving consequence in new drug screening. This model, therefore, may be more predictive of clinical efficacy of novel pharmacological tools than other chronic or acute OA models.